For the pair of functions , find (f-g)(3)
f(x)=2x^2+3 g(x)=x-4
what I have so far is
[2(3)^2+3]-(3-4) --->I distributed the negative sign(don't know if that's correct)......... That is legal
3^2=9(2)=18+3=21........... This is incorrect "mathematical" statements.
21-3+4=22
Can anyone confirm please? Thanks
Don't write "bits and pieces" and set them equal! 3^2= 9, but that is NOT equal to 9(2). And that is not equal to 18+ 3.For the pair of functions , find (f-g)(3)
f(x)=2x^2+3 g(x)=x-4
what I have so far is
[2(3)^2+3]-(3-4) --->I distributed the negative sign(don't know if that's correct)
3^2=9(2)=18+3=21
21-3+4=22
Can anyone confirm please? Thanks